Students' motivation for rubric use in the EFL classroom assessment environment - He, Chunxiu; Zeng, Jiayan; Chen, Jianlin (Frontiers in Psychology, 2022)
The effectiveness of a rubric depends on the enactment by its users. This qualitative study attempts to understand students’ individual differences in rubric use and explore motivation that influences students’ effort devoted to the use in the EFL classroom assessment environment. Seventy-nine students at a Chinese university participated in the study. The data collected included their classroom performance results and nine case study informants’ retrospective interviews on their rubric use in oral presentation tasks. Focuses were drawn upon students’ perceptions and practices of rubric use throughout the task processes in the analysis of their self-reports. Three types of effort patterns emerged in the light of students’ self-ratings and descriptions of the rubric utilization. The intense kind held firm trust in rubric utility and thus was rubric-bound, cautiously attempting to abide by all the criteria throughout the whole process. The medium type either selectively followed the criteria or casually referred to the rubric. The loose type was least responsive to the rubric since their actions seemed more often affected by their self-efficacy and prior experience. Results showed that students’ effort in rubric use in classroom assessment was the end of cognitive appraisals of a rubric, students themselves, and a task. The study supplements concerns on learner and task. Implications on rubric employment and task design are drawn to tap students' task motivation for rubric use in the EFL classroom assessment environment.